The Impact of Leadership on Organizational Citizenship Behavior - Askar, Nancy (International Journal of Economics, Business and Management Studies, 2020)
The research problem is that Small Medium Enterprises are suffering from a decline in performance and the main reason is the absence of the implementation of effective human resources practices including transactional leadership, organizational justice and psychological contract. Additionally, it is also stated that the basis of the following motivational theories is represented by these two theories previously mentioned, because they establish a major difference between intrinsic and extrinsic motivationSmall Medium Enterprises are suffering from a decline in performance and the main reason is the absence of the implementation of effective human resources practices including transactional leadership, organizational justice and psychological contract. The research implemented both the quantitative and qualitative methodologies for data collection throughout distributing the questionnaires over 377 respondents in different Lebanese Small Medium Enterprises. The results will be analyzed using SPSS statistical tool and the AMOS for structure equation modeling. The results proved that psychological contract, transactional leadership and organizational justice are positively correlated with organizational citizenship behavior.